The Pivotal Role of Chemical Modifications in mRNA Therapeutics - Liu, Albert; Wang, Xiao (Frontiers in Cell and Developmental Biology, 2022)
After over a decade of development, mRNA has recently matured into a potent modality for therapeutics. The advantages of mRNA therapeutics, including their rapid development and scalability, have been highlighted due to the SARS-CoV-2 pandemic, in which the first two clinically approved mRNA vaccines have been spotlighted. These vaccines, as well as multiple other mRNA therapeutic candidates, are modified to modulate their immunogenicity, stability, and translational efficiency. Despite the importance of mRNA modifications for harnessing the full efficacy of mRNA drugs, the full breadth of potential modifications has yet to be explored clinically. In this review, we survey the field of mRNA modifications, highlighting their ability to tune the properties of mRNAs. These include cap and tail modifications, nucleoside substitutions, and chimeric mRNAs, each of which represents a component of mRNA that can be exploited for modification. Additionally, we cover clinical and preclinical trials of the modified mRNA platform not only to illustrate the promise of modified mRNAs but also to call attention to the room for diversifying future therapeutics.